DEKONSTRUKSI PEMBERDAYAAN PEREMPUAN DALAM IKLAN WARDAH “OWN YOUR FINISH” (ANALISIS WACANA KRITIS SARA MILLS) - Nazala Adistya Chandra; Chairunnisa Az-zahra' Sulaiman; Rifma Ghulam Dzaljad (PT. Hasba Edukasi Mandiri, 2026)
This study aims to deconstruct the discourse of women's empowerment in Wardah's Own Your Finish advertising campaign using Sara Mills' Critical Discourse Analysis. The campaign was selected because it presents a narrative of women's empowerment by challenging gender stereotypes, particularly through the representation of women in the traditionally masculine sphere of motorsport. This research employs a qualitative method with a descriptive-critical approach. The data consist of static visual elements, including advertising posters, photography, and model poses, as well as verbal elements such as slogans, typography, and advertising copy from the Own Your Finish campaign. Data were analyzed by examining the positions of the subject, object, and reader within the advertising discourse based on Sara Mills' analytical framework. The findings indicate that the campaign constructs an ambivalent discourse of women's empowerment. On one hand, women are represented as autonomous subjects who possess agency, confidence, and the ability to challenge gender stereotypes. On the other hand, the deconstruction of the object position reveals that such empowerment remains embedded within the commercial logic of the beauty industry. Women's strength and independence are commodified while simultaneously required to conform to capitalist beauty standards, such as flawless skin and polished makeup. Furthermore, the reader is positioned to associate personal empowerment with cosmetic consumption, illustrating the practice of commodity feminism. Therefore, the study concludes that the Own Your Finish campaign not only promotes women's empowerment but also transforms feminist values into a marketing strategy that reinforces the commercial interests of the beauty industry.